Quantitative optimization exploration of the cultivation program for medical product management professionals based on QFD-obstacle integration model - Mingming Zhai; Ruochen Feng; Yong Cui; Fang Gao (PLoS ONE, 2026)
Objective The current research on talent cultivation programs for the emerging interdisciplinary field of medical product management in Chinese universities faces the limitation of relying on a single qualitative evaluation, which makes it difficult to meet the growing demand for talent in the industry. This study proposes an innovative framework for the quantitative research on medical product management talent cultivation programs. Using representative domestic universities as empirical cases, it combines qualitative and quantitative methods to assess the quality of talent cultivation programs, laying the foundation for accurately improving the level of medical product management talent training. Methods This study utilized methods such as literature review, expert interviews, and questionnaire surveys to explore the cultivation schemes and competency requirements of professional talent in medical product management. Variance analysis and t-tests were employed to analyze differences in talent needs across different social groups. Based on the Obstacle Degree Model, this research analyzed the obstacles affecting market satisfaction with the cultivation of professionals in medical product management. Further, the study developed a QFD (Quality Function Deployment)-Obstacle Integration Model, which combined the importance of demand with the degree of implementation obstacles to quantify and prioritize the core elements of the talent cultivation program. Results The study established a cultivation system comprising three dimensions: theoretical teaching, practical teaching, and extracurricular activities, as well as a talent competency requirement system including professional integrity, knowledge reserves, and comprehensive capabilities. Differential analysis revealed discrepancies in the perceptions of talent capabilities between employers and students on certain indices ( P < 0.05 ). Satisfaction analysis identified that factors affecting satisfaction were primarily concentrated in the cultivation of professional knowledge and comprehensive skills. Finally, a House of Quality was established, identifying five categories of core elements as the priority improvement directions for the cultivation program (e.g., professional courses, comprehensive practical teaching). Conclusions Based on the analysis results, this study proposes optimization strategies for the cultivation program from three aspects: optimizing curriculum design, enriching training models, and strengthening student guidance. This research not only provides a transferable quantitative optimization tool for the cultivation programs of emerging interdisciplinary fields such as medical product management, but also expands the application paradigm of QFD in complex educational systems, advancing the methodological development of this field from a “single demand-driven” approach to a “demand-obstacle dual-driven” one.